Will Quintrell and The Royal Syncopators, Regent Theatre, Sydney (1910)
"Will Quintrell and The Royal Syncopators - Regent Theatre, Sydney. L to R: Back row - Dick Porter - trumpet ; middle row - Keith Lester - horn ; Bill Smith - sax ; Sammy Cope - drums ; Frank Bull - piano. Front row: Will Quintrell - leader ; Will James - banjo (father of Barbara James) ; Jock Thompson - sax ; clarinet -?" --Printed on label.
Title supplied by donor see file 301/13/00014.
Condition: Good.
Lent for copying.
Part of the collection: Lewis collection of photographs.
Also available online
Keywords: Quintrell, Will -- Portraits; James, Will -- Photographs; Band musicians -- Australia -- Photographs; Jazz musicians -- Australia -- Photographs; Big bands -- Australia -- Photographs; Musicians